The Worm and the Ecologist: Experiencing Planetarity with Frank Herbert’s Dune - Pierre-Louis Patoine (Transatlantica)
This article explores how Frank Herbert’s 1965 novel Dune offers occasions for the development of an ecological, Gaian sensitivity, pushing the human sensorium towards the planetary (in relation to, and contradistinction to, the global, colonial, and imperial imaginaries) by using tools typical of fantasy and science fiction, such as world-building, immersion, sensationalism, terrain navigation, non-modern epistemologies, oneiric possession, geological actants, dragon-like giant sandworms, and human-eating birds. In the novel, these motifs assemble to form thick situations, in which immersed, empathic readers can experience aspects of planetary ecology, thanks to embodied cognition and its sensory and motor simulations.